Comprehensive miRNome-Wide Profiling in a Neuronal Cell Model of Synucleinopathy Implies Involvement of Cell Cycle Genes - Findeiss, Elisabeth (Front Cell Dev Biol, 2021)
Growing evidence suggests that epigenetic mechanisms like microRNA-mediated transcriptional regulation contribute to the pathogenesis of parkinsonism. In order to study the influence of microRNAs (miRNAs), we analyzed the miRNome 2 days prior to major cell death in α-synuclein-overexpressing Lund human mesencephalic neurons, a well-established cell model of Parkinson’s disease (PD), by next-generation sequencing. The expression levels of 23 miRNAs were significantly altered in α-synuclein-overexpressing cells, 11 were down- and 12 upregulated (P < 0.01; non-adjusted). The in silico analysis of known target genes of these miRNAs was complemented by the inclusion of a transcriptome dataset (BeadChip) of the same cellular system, revealing the G0/G1 cell cycle transition to be markedly enriched. Out of 124 KEGG-annotated cell cycle genes, 15 were present in the miRNA target gene dataset and six G0/G1 cell cycle genes were found to be significantly altered upon α-synuclein overexpression, with five genes up- (CCND1, CCND2, and CDK4 at P < 0.01; E2F3, MYC at P < 0.05) and one gene downregulated (CDKN1C at P < 0.001). Additionally, several of these altered genes are targeted by miRNAs hsa-miR-34a-5p and hsa-miR-34c-5p, which also modulate α-synuclein expression levels. Functional intervention by siRNA-mediated knockdown of the cell cycle gene cyclin D1 (CCND1) confirmed that silencing of cell cycle initiation is able to substantially reduce α-synuclein-mediated cytotoxicity. The present findings suggest that α-synuclein accumulation induces microRNA-mediated aberrant cell cycle activation in post-mitotic dopaminergic neurons. Thus, the mitotic cell cycle pathway at the level of miRNAs might offer interesting novel therapeutic targets for PD.